PENGARUH INVOLVEMENT, FAMILIARITY, BRAND LOYALTY DAN PRICE SENSITIVITY TERHADAP CONSUMER EVALUATION PADA PEMBELIAN PRODUK SUSU BUBUK - VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2008)
The main purpose of the research is to examine the influence of involvement, familiarity, brand loyalty and price sensitivity on consumer evaluation. Data was collected using survey questionnaire distribution to 100 respondents. The respondent of the research is people who buy Pediasure powder milk from Abbot Laboratories for their children. Data were analyzed using mul-tiple regression analysis. The result showed that there is significant influence of involvement, familiarity and brand loyalty on consumer evaluation. The result also showed that price sensitivity does not bring any effect on consumer evaluation. Price is not one of the factor considerations for people in buying Pediasure powder milk.